THE INFLUENCE OF TAX INCENTIVES, TAX RATE CHANGES, AND THE NIK-NPWP CONSOLIDATION PROGRAM ON THE COMPLIANCE OF MSME TAXPAYERS (A Study on MSME Actors in BSD City Modern Market) - Reginaldus Elfridus Lobo; Febrian Kwarto (Transpublika Publisher, 2024)
Tax is an essential source of state revenue, but the level of tax compliance, especially in the Micro, Small, and Medium Enterprises (MSMEs) sector, is still relatively low. This study aims to evaluate the effect of tax incentives, changes in tax rates, and the NIK-NPWP matching program on MSME taxpayer compliance in the BSD City Modern Market. Using a quantitative approach, this study involved 90 respondents from a total population of 846 MSMEs, with an accidental sampling technique. Data were analyzed using multiple linear regression through the SPSS 29.0 for Windows program. The findings of the study indicate that tax incentives, changes in tax rates, and the NIK-NPWP matching program have a positive and significant effect on the level of MSME taxpayer compliance in the BSD City Modern Market.